Method for preparing high-performance carbon capture material by using steel slag leachate
By proportioning the metal elements in the steel slag leaching liquid and combining it with all cotton fiber materials, high-performance carbon capture materials were prepared, which solved the problems of poor CO2 capture capability and reduced circulation performance of steel slag materials in the prior art, and achieved efficient and stable CO2 adsorption effect.
Patent Information
- Application Number
- CN202411734669.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-14
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, carbon capture materials prepared by single steel slag or steel slag leaching liquid have poor capture capacity for CO2, and sintering is prone to occur after multiple adsorption-regeneration cycles, resulting in a degradation of performance.
By proportioning the leaching concentrations of Fe, Mn, Ca, Mg, and Al elements in the steel slag leaching solution, soluble iron salts, manganese salts, calcium salts, magnesium salts, and aluminum salts are added to form uniformly porous all cotton fiber material as biological templates, and high-performance carbon capture materials are prepared.
The adsorption amount of CO2 reached 0.45 g/g at 600°C, and the adsorption performance of 0.4 g/g was maintained after 10 adsorption-regeneration cycles, which significantly improved the stability and capture efficiency of the material.
Smart Images

Figure CN119524802A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of CO2 adsorption capture materials, and in particular relates to a method for preparing a high-performance carbon capture material by utilizing steel slag leaching solution. Background Art
[0002] Against the backdrop of the increasing depletion of fossil energy and increasingly severe environmental problems worldwide, finding renewable resources to replace traditional fossil energy and developing efficient and environmentally friendly carbon capture technologies have become important directions for scientific research and industrial applications. Although traditional carbon capture technologies, such as chemical absorption, physical adsorption and membrane separation, can capture CO2 to a certain extent, they often have problems such as high energy consumption, low efficiency, high cost and possible secondary pollution. For example, methanol, as a basic chemical raw material, is widely used in many fields such as solvents, fuels and chemical production. Bamboo biomass, with its rapid growth, strong resource regeneration ability and environmental friendliness, has become an important choice to replace traditional fossil raw materials in the production of methanol. Bamboo biomass to methanol technology not only realizes the efficient conversion and utilization of bamboo resources, but also promotes the recycling of carbon and reduces greenhouse gas emissions. Under the global energy structure transformation and carbon neutrality goals, bamboo biomass to methanol technology has broad development prospects and important strategic significance. In this process, how to effectively capture and utilize the carbon dioxide (CO2) produced in the process is the key to achieving green chemistry and circular economy.
[0003] The steel industry is a major energy-consuming industry and a major source of greenhouse gas emissions. Steel slag is an industrial solid waste generated by steel mills. my country has the largest steel industry in the world, but the utilization rate of steel slag is only 30%. A large amount of steel slag is abandoned, resulting in the waste of valuable materials or energy in it, and occupying land resources. The heavy metal elements in it will also cause damage to the environment. Studies have found that steel slag is a good source of calcium with good mineral carbonization ability. In addition, steel slag carbonization can also solve the problems of poor volume stability and high heavy metal content of steel slag.
[0004] However, investigations have revealed that in the prior art, carbon capture materials prepared solely using steel slag or steel slag leachate usually have the disadvantage of poor CO2 capture capacity, and are prone to severe sintering problems after multiple adsorption-regeneration cycles, especially under high temperature and high CO2 concentration adsorption conditions, which can easily lead to a rapid decrease in the CO2 capture capacity of such carbon capture materials.
[0005] In order to solve the above problems, existing researchers mostly improve the carbon capture performance of the prepared adsorbent material by synergizing, modifying or calcining steel slag with other materials. For example, the Chinese invention patent application "A solid carbon dioxide adsorbent and its preparation method" (CN118122286A) discloses a solid carbon dioxide adsorbent and its preparation method. First, fly ash and steel slag are calcined at high temperature to generate micropores, and then coke powder, zinc oxide and acrylic acid are mixed to shape and calcine at high temperature in the absence of oxygen to form partial mesopores and more micropores. After a period of time, oxygen is introduced to continue calcination to form more mesopores. Finally, a mixture of surfactants and organic amines is sprayed on its surface. The two have a synergistic effect and can improve the carbon dioxide adsorption and cyclic stability performance.
[0006] However, in the above-mentioned prior art, we still noticed that due to the limitations of steel slag itself, it is usually necessary to adopt a more complicated treatment process, or to add a large amount of other materials in a coordinated manner to improve the carbon capture performance of the prepared adsorption material. These methods have invisibly greatly increased the raw material and preparation cost of carbon capture materials using steel slag as raw material, limiting its application value and market prospects.
[0007] Therefore, there is an urgent need for a new high-temperature carbon capture material based on steel slag, which has the advantages of lower cost and simple preparation method, and can efficiently and stably adsorb CO2 in multiple adsorption-regeneration cycles. Summary of the invention
[0008] In order to solve the problems in the above-mentioned prior art, the present invention provides a method for preparing a high-performance carbon capture material using steel slag leachate, which utilizes the proportions of various metal elements in the steel slag leachate to prepare a high-performance carbon capture material using a uniform porous cotton fiber material as a biological template. The adsorption capacity of CO2 at 600°C can reach 0.45g / g, and after 10 subsequent adsorption-regeneration cycles, it can still maintain 0.4g / g, and the adsorption performance is stable.
[0009] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.
[0010] A method for preparing high-performance carbon capture materials using steel slag leachate mainly comprises the following steps:
[0011] (1) subjecting the recovered steel slag to a pretreatment including crushing to obtain a powder to be leached with a particle size of 40 to 100 meshes;
[0012] (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leaching solution;
[0013] (3) according to the leaching concentration of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate obtained in step (2), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate, so that the molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg in the obtained mixed solution meet 9.5-10.5, 49-51, 9.5-10.5 and 10-100 respectively, and the leaching concentration of calcium element is 100-107.5 g / L;
[0014] (4) impregnating the cotton fiber material in the mixed solution obtained in step (3), and performing an impregnation treatment for 24 to 30 hours to obtain an impregnated intermediate product;
[0015] (5) The impregnated intermediate product obtained in step (4) is calcined to obtain a high-performance carbon capture material.
[0016] In this article, the steel slag described in step (1) is an industrial solid waste generated during the steelmaking process. It should be noted that, depending on the different steelmaking processes, the steel slag produced has different particle sizes. Before recycling and reuse, it should be crushed to reduce and homogenize its particle size and improve its reuse value. Generally speaking, in this article, it should be crushed to a particle size of no more than 100 meshes because it needs to be acid-leached to obtain a steel slag leachate. It should be supplemented that there are currently commercially available powders that are obtained by crushing steel slag. The present invention can also directly select such commercially available powders that meet the specification of a particle size of no more than 100 meshes.
[0017] In this article, the steel slag described in step (1) is pre-treated including crushing, and the crushing method is a conventional ore raw material crushing process; depending on the source of the steel slag, technical personnel in this field should know that conventional steel slag pretreatment technology is a prerequisite technology for resource utilization of steel slag, so in addition to crushing, it usually also includes necessary conventional pretreatment of steel slag. Technical personnel in this field can consult the existing technology related to the steelmaking process for processing, which will not be repeated here.
[0018] In this article, the powder to be leached in step (2) is treated with acid leaching to obtain a slag leachate, which is mainly aimed at extracting metal elements from the slag by acid leaching to obtain the slag leachate, which is one of the conventional treatment methods for resource utilization of slag. Those skilled in the art can select suitable acid leaching solutions and acid leaching processes according to existing technical documents or conventional processes. It should be noted that the main purpose of the present invention is to utilize the complex special ratio of metal elements in the slag leachate to meet the preparation of high-performance carbon capture materials. Therefore, although the selection of acid leaching solutions and acid leaching processes will affect the concentration of metal elements in the slag leachate and the leaching efficiency, the above-mentioned effects can be adjusted and selected through existing technologies, which is not the main inventive point of the present invention.
[0019] In order to better illustrate the present invention and provide a technical solution for reference under laboratory conditions, the powder to be leached in step (2) is treated with acid leaching, wherein the acid leaching treatment specifically comprises first preparing 100 mL of acetic acid solution with a concentration of 7 to 8 mol / L, heating it to 70 to 85° C. in a water bath, adding 5 g of the powder to be leached, maintaining the water bath temperature and stirring and mixing for 1 to 1.5 hours, and filtering to obtain a steel slag leachate after the time is up.
[0020] In this article, the leaching concentration of Fe, Mn, Ca, Mg, and Al elements in the steel slag leachate obtained according to step (2) in step (3), wherein the leaching concentration of Fe, Mn, Ca, Mg, and Al elements is obtained by a conventional metal element analysis method in a solution in the chemical industry, for example, by ultraviolet-visible spectrophotometer, atomic absorption spectrometry, X-ray fluorescence spectrometry, or inductively coupled plasma mass spectrometry.
[0021] It should be noted that due to the different sources of steel slag, the leaching concentrations of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate from different sources of steel slag may be different. If necessary, in one of the technical solutions, the steel slag leachate can be diluted or concentrated to be as close to the requirements of the present invention as possible (the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg satisfy 9.5-10.5, 49-51, 9.5-10.5 and 10-100 respectively, and the leaching concentration of calcium element is 100-107.5 g / L).
[0022] In this article, in step (3), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate. Whether to add the above-mentioned iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts and how much to add are all based on whether the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg are 9.5-10.5, 49-51, 9.5-10.5 and 10-100 respectively, and the leaching concentration of calcium element is 100-107.5 g / L. If the current metal element already meets the above requirements, the corresponding metal salt is not added. If the above requirements are not met, the corresponding metal salt is added.
[0023] For better explanation, taking the steel slag leachate used in the embodiment of the present invention as an example, the Shimadzu UV-2600 ultraviolet-visible spectrophotometer was used to analyze Fe, Mn, Ca, Mg, and Al in the steel slag leachate, and the leaching concentration of Fe element was 2.69 g / L, the leaching concentration of Mn element was 0.53 g / L, the leaching concentration of Ca element was 9 g / L, the leaching concentration of Mg element was 0.12 g / L, and the leaching concentration of Al element was 1.3 g / L. According to the required leaching concentration of calcium element of 100-107.5 g / L, 47.32-51.22 g of hydrated calcium acetate was added thereto as a calcium salt, and according to the required Ca:Mg molar ratio of 10-100, 0-0.92 g of magnesium acetate tetrahydrate was added thereto as a magnesium salt, without adding iron salt, manganese salt and aluminum salt.
[0024] In this article, the iron salt, manganese salt, calcium salt, magnesium salt and aluminum salt in step (3) are conventional metal salt raw materials in the chemical industry. It should be noted that the metal salt that can be dissolved in the steel slag leachate should be selected.
[0025] In one of the technical solutions, the iron salt selected in step (3) includes any one or more of ferric nitrate nonahydrate, ferric chloride hexahydrate, and ferric acetate tetrahydrate.
[0026] In one technical solution, the manganese salt in step (3) is selected from any one or more of manganese nitrate solution, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate.
[0027] In one technical solution, the calcium salt selected in step (3) includes any one or more of hydrated calcium acetate and calcium nitrate tetrahydrate.
[0028] In one technical solution, the magnesium salt selected in step (3) includes any one or more of magnesium acetate tetrahydrate and magnesium nitrate hexahydrate.
[0029] In one of the technical solutions, the aluminum salt selected in step (3) includes any one or more of aluminum nitrate nonahydrate and aluminum chloride hexahydrate.
[0030] In this article, the pure cotton fiber material described in step (4) is selected as a carrier of conventional adsorption materials. After roasting, a porous structure is formed, which is selected as a carrier of conventional carbon capture materials. Under laboratory conditions, cosmetic cotton sheets can be selected as pure cotton fiber materials.
[0031] It should be noted that, since the mixed solution obtained in step (3) may precipitate when left to stand, if the operation is not continuous, it is recommended to stir the mixed solution at 70° C. for at least 30 min before the immersion treatment in step (4).
[0032] In one of the technical solutions, in order to improve the impregnation effect, the impregnation treatment in step (4) is carried out under closed conditions and accompanied by stirring; wherein the stirring is preferably mechanical stirring at 300 to 500 r / min.
[0033] In this article, the impregnated intermediate product in step (5) is calcined to obtain a high-performance carbon capture material, wherein calcination is a conventional process for preparing carbon capture materials. Based on the cotton fiber material selected as the carrier in the present invention, its specific calcination process parameters can directly refer to the conventional calcination parameters of the carrier.
[0034] In order to better illustrate the present invention and provide a technical solution for reference, the calcination in step (5) is specifically to increase the temperature to 750-800° C. at a rate of 5-10° C. / min and calcine for 2-4 hours.
[0035] The main inventive point of the present invention is that based on the rich metal elements in the steel slag of industrial solid waste, the positive influence of the ratio control of metal elements in its leachate on the preparation of carbon capture materials is systematically studied for the first time. Based on its leachate, a set of fixed ratios of Fe, Mn, Ca, Mg, and Al elements is provided. Through this ratio, technicians can quantitatively add metal salts to the steel slag leachate, so as to prepare high-performance carbon capture materials based on steel slag from different sources as a single raw material in a simple and fast way, which can efficiently and stably adsorb CO2 in multiple adsorption-regeneration cycles. Comparative experiments have confirmed that the carbon capture material samples prepared by impregnation of mixed liquor with adjusted metal element ratios have obvious advantages in CO2 adsorption capacity and cyclic capture capacity compared with the comparative samples prepared by unadjusted steel slag leachate.
[0036] After further comparative tests, it was surprisingly found that compared with the carbon capture material comparison sample prepared by impregnation with the verification solution obtained by dissolving metal salts with the same metal element ratio, the embodiment of the present invention still has a relatively obvious advantage. It is speculated that this is because the trace metal elements in the steel slag promote the carbon capture ability. Therefore, the present invention provides a new way to recycle and reuse steel slag with high value, and can serve as the foundation for the subsequent technical development.
[0037] In addition, through research, analysis and experiments, it was found that when steel slag from different sources is used as the raw material of the present invention, it is usually only necessary to supplement calcium salts with lower costs and some magnesium salts according to actual conditions, while the demand for iron salts, manganese salts and aluminum salts is usually negligible, and other additives are usually not required. The present invention uses all-cotton fiber material as the impregnation carrier, which has a uniform and rich internal pore structure and low price, and has significant advantages in preparation cost.
[0038] It is worth noting that due to the limitation of experimental conditions, only pure cotton fiber materials available under laboratory conditions were used in the selection of carriers. Theoretically, there is still a lot of room for optimization in the selection of carriers. Based on the concept of seeking truth from facts, the present invention does not protect theoretical methods that have not been experimentally verified.
[0039] The present invention has the following beneficial effects:
[0040] 1. The present invention provides a method for preparing a high-performance carbon capture material using steel slag leachate, which uses the proportions of various metal elements in the steel slag leachate to prepare a high-performance carbon capture material using a uniform porous cotton fiber material as a biological template. The CO2 adsorption capacity at 600°C can reach 0.45g / g, and can still maintain 0.4g / g after 10 subsequent adsorption-regeneration cycles, and the adsorption performance is stable.
[0041] 2. The present invention provides a method for preparing high-performance carbon capture materials using steel slag leachate, which improves the adsorption capacity of carbon capture materials by utilizing a fixed ratio of Fe, Mn, Ca, Mg, and Al elements in the steel slag leachate.
[0042] 3. The overall process of the present invention is simple and easy to operate, the raw material cost is very low, and the material has good adsorption effect and stable adsorption performance. It has excellent application prospects, provides a new way for high-value recycling and reuse of steel slag, and can serve as the foundation for subsequent technological development. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 These are actual photos of the steel slag powder, steel slag leaching solution, intermediate products after immersion, and the high-performance carbon capture material finally prepared in Example 1 of the present invention.
[0044] Figure 2 This is a line graph characterizing the adsorption capacity of the sample of Example 1 of the present invention for CO2.
[0045] Figure 3 This is a line graph characterizing the cyclic adsorption capacity of CO2 of the sample in Example 1 of the present invention.
[0046] Figure 4 This is a line graph characterizing the adsorption capacity of CO2 of the sample of Example 2 of the present invention.
[0047] Figure 5 This is a line graph characterizing the cyclic adsorption capacity of CO2 of the sample in Example 2 of the present invention.
[0048] Figure 6 This is a line graph characterizing the adsorption capacity of CO2 for the comparative sample prepared in Comparative Example 1 of the present invention.
[0049] Figure 7This is a line graph characterizing the adsorption capacity of CO2 for the verification comparison sample prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0050] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.
[0051] A method for preparing high-performance carbon capture materials using steel slag leachate mainly comprises the following steps:
[0052] (1) subjecting the recovered steel slag to a pretreatment including crushing to obtain a powder to be leached with a particle size of 40 to 100 meshes;
[0053] (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leachate;
[0054] (3) according to the leaching concentration of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate obtained in step (2), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate, so that the molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg in the obtained mixed solution meet 9.5-10.5, 49-51, 9.5-10.5 and 10-100 respectively, and the leaching concentration of calcium element is 100-107.5 g / L;
[0055] (4) impregnating the cotton fiber material in the mixed solution obtained in step (3), and performing an impregnation treatment for 24 to 30 hours to obtain an impregnated intermediate product;
[0056] (5) The impregnated intermediate product obtained in step (4) is calcined to obtain a high-performance carbon capture material.
[0057] In this article, the steel slag described in step (1) is an industrial solid waste generated during the steelmaking process. It should be noted that, depending on the different steelmaking processes, the steel slag produced has different particle sizes. Before recycling and reuse, it should be crushed to reduce and homogenize its particle size and improve its reuse value. Generally speaking, in this article, it should be crushed to a particle size of no more than 100 meshes because it needs to be acid-leached to obtain a steel slag leachate. It should be supplemented that there are currently commercially available powders that are obtained by crushing steel slag. The present invention can also directly select such commercially available powders that meet the specification of a particle size of no more than 100 meshes.
[0058] In this article, the steel slag described in step (1) is pre-treated including crushing, and the crushing method is a conventional ore raw material crushing process; depending on the source of the steel slag, technical personnel in this field should know that conventional steel slag pretreatment technology is a prerequisite technology for resource utilization of steel slag, so in addition to crushing, it usually also includes necessary conventional pretreatment of steel slag. Technical personnel in this field can consult the existing technology related to the steelmaking process for processing, which will not be repeated here.
[0059] In this article, the powder to be leached in step (2) is treated with acid leaching to obtain a slag leachate, which is mainly aimed at extracting metal elements from the slag by acid leaching to obtain the slag leachate, which is one of the conventional treatment methods for resource utilization of slag. Those skilled in the art can select suitable acid leaching solutions and acid leaching processes according to existing technical documents or conventional processes. It should be noted that the main purpose of the present invention is to utilize the complex special ratio of metal elements in the slag leachate to meet the preparation of high-performance carbon capture materials. Therefore, although the selection of acid leaching solutions and acid leaching processes will affect the concentration of metal elements in the slag leachate and the leaching efficiency, the above-mentioned effects can be adjusted and selected through existing technologies, which is not the main inventive point of the present invention.
[0060] In order to better illustrate the present invention and provide an implementation method for reference under laboratory conditions, the powder to be leached in step (2) is treated with acid leaching, wherein the acid leaching treatment specifically comprises first preparing 100 mL of acetic acid solution with a concentration of 7 to 8 mol / L, heating it to 70 to 85° C. in a water bath, adding 5 g of the powder to be leached, maintaining the water bath temperature and stirring and mixing for 1 to 1.5 hours, and filtering to obtain a steel slag leachate after the time is up.
[0061] In this article, the leaching concentration of Fe, Mn, Ca, Mg, and Al elements in the steel slag leachate obtained according to step (2) in step (3), wherein the leaching concentration of Fe, Mn, Ca, Mg, and Al elements is obtained by a conventional metal element analysis method in a solution in the chemical industry, for example, by ultraviolet-visible spectrophotometer, atomic absorption spectrometry, X-ray fluorescence spectrometry, or inductively coupled plasma mass spectrometry.
[0062] It should be noted that due to the different sources of steel slag, the leaching concentrations of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate from different sources of steel slag may be different. If necessary, in one embodiment, the steel slag leachate can be diluted or concentrated to be as close to the requirements of the present invention as possible (the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg satisfy 9.5-10.5, 49-51, 9.5-10.5 and 10-100 respectively, and the leaching concentration of calcium element is 100-107.5 g / L).
[0063] In this article, in step (3), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate. Whether to add the above-mentioned iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts and how much to add are all based on whether the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg are 9.5-10.5, 49-51, 9.5-10.5 and 10-100 respectively, and the leaching concentration of calcium element is 100-107.5 g / L. If the current metal element already meets the above requirements, the corresponding metal salt is not added. If the above requirements are not met, the corresponding metal salt is added.
[0064] For better explanation, taking the steel slag leachate used in the embodiment of the present invention as an example, the Shimadzu UV-2600 ultraviolet-visible spectrophotometer was used to analyze Fe, Mn, Ca, Mg, and Al in the steel slag leachate, and the leaching concentration of Fe element was 2.69 g / L, the leaching concentration of Mn element was 0.53 g / L, the leaching concentration of Ca element was 9 g / L, the leaching concentration of Mg element was 0.12 g / L, and the leaching concentration of Al element was 1.3 g / L. According to the required leaching concentration of calcium element of 100-107.5 g / L, 47.32-51.22 g of hydrated calcium acetate was added thereto as a calcium salt, and according to the required Ca:Mg molar ratio of 10-100, 0-0.92 g of magnesium acetate tetrahydrate was added thereto as a magnesium salt, without adding iron salt, manganese salt and aluminum salt.
[0065] In this article, the iron salt, manganese salt, calcium salt, magnesium salt and aluminum salt in step (3) are conventional metal salt raw materials in the chemical industry. It should be noted that the metal salt that can be dissolved in the steel slag leachate should be selected.
[0066] In one embodiment, the iron salt selected in step (3) includes any one or more of ferric nitrate nonahydrate, ferric chloride hexahydrate, and ferric acetate tetrahydrate.
[0067] In one embodiment, the manganese salt in step (3) includes any one or more of manganese nitrate solution, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate.
[0068] In one embodiment, the calcium salt selected in step (3) includes any one or more of hydrated calcium acetate and calcium nitrate tetrahydrate.
[0069] In one embodiment, the magnesium salt selected in step (3) includes any one or more of magnesium acetate tetrahydrate and magnesium nitrate hexahydrate.
[0070] In one embodiment, the aluminum salt selected in step (3) includes any one or more of aluminum nitrate nonahydrate and aluminum chloride hexahydrate.
[0071] In this article, the pure cotton fiber material described in step (4) is selected as a carrier of conventional adsorption materials. After roasting, a porous structure is formed, which is selected as a carrier of conventional carbon capture materials. Under laboratory conditions, cosmetic cotton sheets can be selected as pure cotton fiber materials.
[0072] It should be noted that, since the mixed solution obtained in step (3) may precipitate when left to stand, if the operation is not continuous, it is recommended to stir the mixed solution at 70° C. for at least 30 min before the immersion treatment in step (4).
[0073] In one embodiment, in order to improve the impregnation effect, the impregnation treatment in step (4) is carried out under closed conditions and accompanied by stirring; wherein the stirring is preferably mechanical stirring at 300 to 500 r / min.
[0074] In this article, the impregnated intermediate product in step (5) is calcined to obtain a high-performance carbon capture material, wherein calcination is a conventional process for preparing carbon capture materials. Based on the cotton fiber material selected as the carrier in the present invention, its specific calcination process parameters can directly refer to the conventional calcination parameters of the carrier.
[0075] In order to better illustrate the present invention and provide an implementation method for reference, the calcination in step (5) is specifically to increase the temperature to 750-800° C. at a rate of 5-10° C. / min and calcine for 2-4 hours.
[0076] The main inventive point of the present invention is that based on the rich metal elements in the steel slag of industrial solid waste, the positive influence of the ratio control of metal elements in its leachate on the preparation of carbon capture materials is systematically studied for the first time. Based on its leachate, a set of fixed ratios of Fe, Mn, Ca, Mg, and Al elements is provided. Through this ratio, technicians can quantitatively add metal salts to the steel slag leachate, so as to prepare high-performance carbon capture materials based on steel slag from different sources as a single raw material in a simple and fast way, which can efficiently and stably adsorb CO2 in multiple adsorption-regeneration cycles. Comparative experiments have confirmed that the carbon capture material samples prepared by impregnation of mixed liquor with adjusted metal element ratios have obvious advantages in CO2 adsorption capacity and cyclic capture capacity compared with the comparative samples prepared by unadjusted steel slag leachate.
[0077] After further comparative tests, it was surprisingly found that compared with the carbon capture material comparison sample prepared by impregnation with the verification solution obtained by dissolving metal salts with the same metal element ratio, the embodiment of the present invention still has a relatively obvious advantage. It is speculated that this is because the trace metal elements in the steel slag promote the carbon capture ability. Therefore, the present invention provides a new way to recycle and reuse steel slag with high value, and can serve as the foundation for the subsequent technical development.
[0078] In addition, through research, analysis and experiments, it was found that when steel slag from different sources is used as the raw material of the present invention, it is usually only necessary to supplement calcium salts with lower costs and some magnesium salts according to actual conditions, while the demand for iron salts, manganese salts and aluminum salts is usually negligible, and other additives are usually not required. The present invention uses all-cotton fiber material as the impregnation carrier, which has a uniform and rich internal pore structure and low price, and has significant advantages in preparation cost.
[0079] It is worth noting that due to the limitation of experimental conditions, only pure cotton fiber materials available under laboratory conditions were used in the selection of carriers. Theoretically, there is still a lot of room for optimization in the selection of carriers. Based on the concept of seeking truth from facts, the present invention does not protect theoretical methods that have not been experimentally verified.
[0080] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.
[0081] Example
[0082] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.
[0083] 1. Raw materials
[0084] The steel slag powder is provided by Henan Borun Casting Materials Co., Ltd. The particle size of the steel slag powder is 40-100 meshes. The main chemical composition is shown in Table 1:
[0085] Table 1 Main chemical composition of steel slag
[0086]
[0087] The reagents used are shown in Table 2 below:
[0088] Material Name concentration Manufacturer <![CDATA[CH3COOH]]> Analytical grade Shanghai MacLean Biochemical Technology Co., Ltd. <![CDATA[Ca(C2H3O2)2·H2O]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. <![CDATA[Mg(C2H3O2)2·4H2O]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. Cosmetic cotton pads Cotton Shenzhen Cotton Times Technology Co., Ltd.
[0089] 2. Preparation method
[0090] (1) directly using steel slag powder with a particle size of 40 to 100 mesh as the powder to be leached;
[0091] (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leachate;
[0092] The acid leaching treatment specifically comprises the following steps: firstly preparing 100 mL of acetic acid solution with a concentration of 7 mol / L, heating it to 70°C in a water bath, adding 5 g of the powder to be leached, maintaining the water bath temperature and stirring and mixing for 1 hour, and filtering to obtain the steel slag leachate after the time is up;
[0093] (3) According to the steel slag leachate obtained in step (2), the Fe, Mn, Ca, Mg and Al in the steel slag leachate are analyzed by Shimadzu UV-2600 ultraviolet-visible spectrophotometer, and the leaching concentration of the Fe element is 2.69 g / L, the leaching concentration of the Mn element is 0.53 g / L, the leaching concentration of the Ca element is 9 g / L, the leaching concentration of the Mg element is 0.12 g / L, and the leaching concentration of the Al element is 1.3 g / L. According to the required leaching concentration of the calcium element of 100 g / L, 47.32 g of hydrated calcium acetate is added as a calcium salt, and according to the required molar ratio of Ca:Mg of 10 to 100, 0 to 0.92 g of magnesium acetate tetrahydrate is added as a magnesium salt, and no iron salt, manganese salt and aluminum salt need to be added to obtain a mixed solution;
[0094] (4) dipping the cosmetic cotton sheet in the mixed solution obtained in step (3) for 24 hours to obtain an intermediate product after dipping;
[0095] The impregnation treatment is carried out under closed conditions and accompanied by stirring;
[0096] (5) preparing a high-performance carbon capture material by calcining the impregnated intermediate product obtained in step (4);
[0097] The calcination is specifically carried out by heating the temperature to 750° C. at a rate of 10° C. / min and calcining for 2 hours.
[0098] 3. Test Methods
[0099] (1) Thermogravimetric analysis (TG: CO2 adsorption capacity test)
[0100] 10 mg of powdered carbon capture material was weighed and the adsorption capacity and cyclic adsorption stability were evaluated in a thermogravimetric analyzer. The experimental conditions were: heating to 920°C at 10°C / min in a N2 atmosphere, calcining for 20 min, then cooling to 600°C at 10°C / min, switching to a CO2 atmosphere, and adsorbing for 20 min.
[0101] The calculation formula for CO2 adsorption capacity is as follows:
[0102]
[0103] Where N is the number of cycles; C N Indicates the CO2 capture capacity of the sample in the Nth cycle, g / g; m carb,N and m 0,N Represent the mass of the sample after the Nth carbonization and calcination reaction, g.
[0104] (2) Nitrogen physical adsorption (BET: specific surface area test)
[0105] 1 g of powdered carbon capture material was weighed, and the specific surface area was measured in a fully automatic specific surface and porosity analyzer. The experimental conditions were as follows: before the sample was tested, it was vacuum degassed at 300°C for 3 h to remove substances such as water and air adsorbed on the sample surface, and then adsorption / desorption was carried out at liquid nitrogen temperature (77K) to obtain the nitrogen adsorption-desorption isotherm. The specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method, and the pore volume and pore size distribution were calculated using the Barrett-Joyner-Halenda (BJH) method.
[0106] Example 1
[0107] Example 1 is in accordance with the above-mentioned "2. Preparation method" steps, wherein according to the required Ca:Mg molar ratio of 10, 0.92 g of magnesium acetate tetrahydrate is added as magnesium salt to prepare a high-performance carbon capture material as a sample.
[0108] According to tests, the adsorption capacity of CO2 can reach 0.45g / g at 600℃, and the adsorption capacity can still be stabilized at around 0.4g / g after 10 subsequent adsorption-regeneration processes.
[0109] Specific test results are as follows Figures 1-2 As shown in Table 3 below:
[0110] Table 3 Circulation capture capacity of CO2 of samples in Example 1
[0111] Cycle times / times Adsorption capacity g / g 1 0.45287 2 0.43294 3 0.4047 4 0.40323 5 0.40323 6 0.40204 7 0.40095 8 0.40095 9 0.40011 1δ 0.4001
[0112] Example 2
[0113] Example 2 follows the steps of “2. Preparation method” above, wherein the required molar ratio of Ca:Mg is 100 and no magnesium salt is added to prepare a high-performance carbon capture material as a sample.
[0114] According to the test, the adsorption capacity of CO2 can reach 0.34g / g at 600℃, and the adsorption capacity can still be stabilized at about 0.3g / g after 10 subsequent adsorption-regeneration processes.
[0115] Specific test results are as follows Figures 3-4 As shown in Table 4 below:
[0116] Table 4 Circulation capture capacity of CO2 of samples in Example 2
[0117] Cycle times / times Adsorption capacity g / g 1 0.3444 2 0.3432 3 0.3321 4 0.3310 5 0.3225 6 0.3223 7 0.3179 8 0.3168 9 0.3150 10 0.3089
[0118] Comparative Example 1
[0119] Comparative Example 1 refers to the steps of the above “2. Preparation method”, but in step (3), no calcium salt and magnesium salt are added, and the subsequent steps are directly performed as the mixed liquid to prepare a carbon capture material as a comparative sample.
[0120] After testing, the adsorption capacity of CO2 of the comparative sample prepared in Comparative Example 1 is as follows: Figure 5 As shown, it is obviously inferior to the samples in Example 1 and Example 2.
[0121] Comparative Example 2
[0122] Comparative Example 2 is a verification comparative example. According to the ratio of Fe, Mn, Ca, Mg and Al elements proposed in the present invention, a carbon capture material prepared by impregnation with a verification solution obtained by dissolving metal salts is used as a verification comparison sample. The specific preparation steps are as follows:
[0123] (1) Weigh 10 g of calcium acetate hydrate, 1.91 g of ferric acetate nonahydrate, 1.76 g of aluminum acetate nonahydrate, 0.24 g of manganese acetate tetrahydrate, and 1.03 g of magnesium acetate tetrahydrate, add them to 100 ml of deionized water, dissolve them, and mix them to prepare a mixed solution;
[0124] (2) dipping the cosmetic cotton sheet in the mixed solution obtained in step (1) for 24 hours to obtain an intermediate product after dipping;
[0125] The impregnation treatment is carried out under closed conditions and accompanied by stirring;
[0126] (3) preparing a carbon capture material by calcining the impregnated intermediate product obtained in step (2);
[0127] The calcination is specifically carried out by heating the temperature to 750° C. at a rate of 10° C. / min and calcining for 2 hours.
[0128] After testing, the adsorption capacity of CO2 of the comparative sample prepared in Comparative Example 2 is as follows: Figure 6 As shown, although the molar ratio and concentration of Fe, Mn, Ca, Mg and Al in the mixed solution are almost consistent with those in Example 1, the carbon capture performance of the sample is still inferior to that of Example 1. It is speculated that this is because the trace metal elements in the steel slag promote the carbon capture ability.
[0129] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing high-performance carbon capture materials using steel slag leachate, characterized in that The main steps include: (1) subjecting the recovered steel slag to a pretreatment including crushing to obtain a powder to be leached with a particle size of 40 to 100 meshes; (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leachate; (3) according to the leaching concentration of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate obtained in step (2), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate, so that the molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg in the obtained mixed solution meet 9.5-10.5, 49-51, 9.5-10.5 and 10-100 respectively, and the leaching concentration of calcium element is 100-107.5 g / L; (4) impregnating the cotton fiber material in the mixed solution obtained in step (3), and performing an impregnation treatment for 24 to 30 hours to obtain an impregnated intermediate product; (5) The impregnated intermediate product obtained in step (4) is calcined to obtain a high-performance carbon capture material.
2. The method according to claim 1, characterized in that: The powder to be leached in step (2) is treated with acid leaching, wherein the acid leaching treatment is specifically to first prepare 100 mL of acetic acid solution with a concentration of 7 to 8 mol / L, heat it to 70 to 85° C. in a water bath, add 5 g of the powder to be leached, maintain the water bath temperature and stir and mix for 1 to 1.5 hours, and filter to obtain the steel slag leachate after the time is up.
3. The method according to claim 1, characterized in that: Step (3) also includes diluting or concentrating the steel slag leachate.
4. The method according to claim 1, characterized in that: The iron salt in step (3) includes any one or more of ferric nitrate nonahydrate, ferric chloride hexahydrate, and ferric acetate tetrahydrate; The manganese salt in step (3) includes any one or more of manganese nitrate solution, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate; The calcium salt in step (3) includes any one or more of hydrated calcium acetate and calcium nitrate tetrahydrate; The magnesium salt in step (3) includes any one or more of magnesium acetate tetrahydrate and magnesium nitrate hexahydrate; The aluminum salt in step (3) includes any one or more of aluminum nitrate nonahydrate and aluminum chloride hexahydrate.
5. The method according to claim 1, characterized in that: The immersion treatment in step (4) is carried out under closed conditions and accompanied by stirring.
6. The method according to claim 1, characterized in that: The calcination in step (5) is specifically to increase the temperature to 750-800°C at a rate of 5-10°C / min and calcine for 2-4h.
7. The high-performance carbon capture material prepared by the method for preparing high-performance carbon capture material using steel slag leaching solution as claimed in claim 1.
8. The high performance carbon capture material as claimed in claim 7 is applied in the field of CO2 adsorption capture.
Citation Information
Patent Citations
Solid carbon dioxide adsorbent and preparation method thereof
CN118122286A